2017
DOI: 10.1002/acm2.12144
|View full text |Cite
|
Sign up to set email alerts
|

The role of CT myelography in sparing the spinal cord during definitive radiotherapy in vertebral hemangioma

Abstract: IntroductionThe spinal cord is poorly visualized on CT images but is well visualized in MRI images. However, implants used for spinal stabilization can produce artifacts on the MRI images which can interfere with identification of the cord. CT myelography in conjunction with CT simulation helps to clearly delineate the cord.Materials and methods CT simulation was done in a patient with vertebral hemangioma. Pre‐ and post myelography images were obtained. Two plans were generated on pre and post myelography CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The administered contrast fills the CSF space around the spinal cord, resulting in good contrast between the spinal cord and CSF so that the spinal cord contours can be delineated. Sudha et al 29 assessed the role of CT myelography in sparing the spinal cord during definitive radiation therapy in vertebral hemangioma. They found that CT myelogram was useful in cases where the tumor margin is in close relation to the spinal cord and in cases of spinal implants that result in MRI distortions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administered contrast fills the CSF space around the spinal cord, resulting in good contrast between the spinal cord and CSF so that the spinal cord contours can be delineated. Sudha et al 29 assessed the role of CT myelography in sparing the spinal cord during definitive radiation therapy in vertebral hemangioma. They found that CT myelogram was useful in cases where the tumor margin is in close relation to the spinal cord and in cases of spinal implants that result in MRI distortions.…”
Section: Discussionmentioning
confidence: 99%
“…A potential imaging method for overcoming this issue is the use of 3-dimensional T2-weighted sequences with small isotropic voxels, such as T2 SPACE. 29 , 30 Our group is currently pursuing a study to compare standard T2-weighted MRI versus T2 Space MRI sequences for spinal cord definition to determine whether this modality may aid in reducing uncertainty at the spinal cord-CSF interface. Differences may also be related to parameters of the CT myelogram, for example, the smoothing algorithm used in the reconstruction based on either a soft tissue versus a bone reconstruction kernel.…”
Section: Discussionmentioning
confidence: 99%
“…Schließlich spielt die CT-Myelografie eine wichtige Rolle bei der Behandlung maligner oder metastasierter Erkrankungen der Wirbelsäule, indem sie die leptomeningeale Beteiligung von Neoplasmen des zentralen Nervensystems oder metastasierten Erkrankungen dar-stellt und bei der Planung der Strahlentherapie hilft. Sie ist insbesondere dann sehr nützlich, wenn die MRT eingeschränkt einsetzbar oder kontraindiziert ist [8][9][10].…”
Section: Indikationen Für Die Ct-myelografieunclassified
“…Last, CT myelography plays an important role in management of spine malignancy or metastatic disease by depicting leptomeningeal involvement of central nervous system neoplasm or metastatic disease and helping plan radiation therapy, especially when MRI is limited or contraindicated (8)(9)(10).…”
Section: Indications For Ct Myelographymentioning
confidence: 99%